EVALUATION OF PROGNOSTIC FACTORS IN QUALITY OF LIFE OF PATIENTS WITH ADOLESCENT IDIOPATHIC SCOLIOSIS UNDERGOING SPINAL FUSION BY THE POSTERIOR APPROACH - POMAR,FELIPE DE MORAES (2016)
ABSTRACT Objective: To evaluate the prognostic factors in the treatment of patients diagnosed with adolescent idiopathic scoliosis undergoing spinal fusion by the posterior approach. Methods: The study included 48 patients with idiopathic adolescent scoliosis (43 females and 5 males) who underwent spinal fusion by the posterior approach, with an average age at diagnosis of 12 years, and clinical signs of Risser between 3 and 4 at the time of surgery. Clinical and radiographic measurements were performed, the participants answered the SRS-30 questionnaire, and the analysis of the medical record data was performed in two occasions during the preoperative period and at the end of two years of follow-up. Results: All satisfaction measures showed statistically significant change after the procedure (p<0.05) with respect to the radiographic characteristics, except for the lumbar apical vertebral translation (p=0.540) and Cobb L1-L5 (p=0.225). Conclusion: In general, it was found that patients who received surgical treatment were more satisfied with their appearance than those who underwent conservative treatment.